Environmental Protection Law and Oil Contracts: Evaluating Iranian Approach Comparing to the International Oil Contracts - Movahedian, Hussein; Norouzi, Nima (Pusat Kajian Hukum Perbankan Fakultas Hukum Universitas Jember, 2024)
Most oil reserves are located in developing countries, which often lack the regulations necessary to comply with international standards. Developing countries have developed the necessary laws and regulations due to new technologies like framing, which are reflected in drilling and development contracts. Study and analysis of the environmental conditions in oil contracts have been conducted in the present article, including the new generation of oil contracts for the Islamic Republic of Iran. This study aims to review the solutions provided in international agreements, analyze the current status of the laws and regulations of the Islamic Republic of Iran, and provide the necessary solutions according to the current situation of oil operations in Iran. In addition to its ethical value, the conclusions of this paper can be useful to policymakers and lawyers involved in oil and gas contracts. In the first part of paper, the environmental effects of oil and gas activities are mentioned; In the second part, the method of forecasting environmental considerations in international oil contracts are examined, and then in the third part, the environmental criteria of Iranian oil contracts are examined. Finally, according to the problems in the adopted methods, a solution is presented.